أهمية استخدام الحاسوب في تعلّم اللغة خاصة لتنمية مهارة القراءة - Penny Respati Yurisa (Institut Agama Islam Negeri (IAIN) Metro, 2017)
Language has been a historical phenomenon in every human civilization. Language has become a widespread object of research. Reading is one of language skill whis is remains the primary means by which educated people gain information, it is difficult to imagine a college course without reading assignments. Reading is a complex cognitive process of decoding symbols in order to construct or derive meaning (reading comprehension). It is a means of language acquisition, of communication, and of sharing information and ideas. Like all languages, it is a complex interaction between the text and the reader which is shaped by the reader’s prior knowledge, experiences, attitude, and language community which is culturally and socially situated. The reading process requires continuous practice, development, and refinement. There are many ways to mastering reading material like using the computer as a modern people. Computer really helps the teacher in process of study. Computer has a positive effect in reaching the aim of teaching. Key words: language, reading and computer.